Answer:
Please look at the explanation!
Explanation:
a. Base case: For n = 1, we have x^1 - y^1 = x - y, which is clearly divisible by x-y.
Inductive step: Assume that for some positive integer k, x^k - y^k is divisible by x-y. We will show that this implies that x^(k+1) - y^(k+1) is also divisible by x-y.
Starting with x^(k+1) - y^(k+1), we can factor out x^k from the first term and y^k from the second term:
x^(k+1) - y^(k+1) = xx^k - yy^k
= x(x^k - y^k) + y^k(x - y)
By our assumption, x^k - y^k is divisible by x-y. Also, x-y is a factor of (x-y), so we can write:
x(x^k - y^k) + y^k(x - y) = (x-y)(x^k - y^k + y^k)
= (x-y)x^k
b. Proof by induction that n(n+1)(n+2) is a multiple of 6.
Base case: For n = 1, we have 1(1+1)(1+2) = 6, which is clearly a multiple of 6.
Inductive step: Assume that for some positive integer k, k(k+1)(k+2) is a multiple of 6. We will show that this implies that (k+1)(k+2)(k+3) is also a multiple of 6.
Starting with (k+1)(k+2)(k+3), we can expand the product:
(k+1)(k+2)(k+3) = k(k+1)(k+2) + 3(k+1)(k+2)
By our assumption, k(k+1)(k+2) is a multiple of 6. Also, 3(k+1)(k+2) is clearly a multiple of 6, since it contains a factor of 3 and a factor of 2. Therefore, (k+1)(k+2)(k+3) is a multiple of 6.